The Impact of Virtual Reality on Motion Sickness Incidents: Causes, Roles, and Prevention Strategies - Wibowo, Auberta Salsabila Ardi; Warasanti, Endang Susanti; Wisnuaji, Lucas (Faculty of Medical - UPN Veteran Jawa Timur, 2024)
Background: Technology is increasingly developing, over time the virtual reality (VR) industry is increasingly in demand. VR is a three-dimensional object that displays the real world. With this sophistication, VR actually provides discomfort for its users, namely Motion Sickness. Motion Sickness is a change in dynamic movement in the virtual world that causes discomfort to its users. Method: The method used in this paper is the literature review method. Purpose: the purpose of this paper is to determine the impact of Virtual Reality on Motion Sickness incidents. Discussion: The results of the literature review show that there are causes of VR Sickness, namely hardware, content, and human factors. VR Sickness can be prevented through pharmacological and non-pharmacological means. Conclusion: Virtual Reality is one of the causes of Motion Sickness incidents.